PENGARUH PEMBIAYAAN MURABAHAH, MUDHARABAH, MUSYARAKAH TERHADAP PROFITABILITAS PADA PT. BANK RAKYAT INDONESIA (BRI) SYARIAH - Ovi Yuhana Putri; Citra Mulyasari (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2022)
Introduction: This research is motivated by financial institutions that have several services offered to the public so that people are interested in using the services of financial institutions because more and more people use the services of these institutions indirectly the community also plays a role in economic growth. PT Bank Rakyat Indonesia (BRI) Syariah offers services with a sharia financing system such as financing products with a basic profit-sharing mechanism.All financing products issued by banks have the aim of being able to provide benefits or increase profitability for the bank. The indicator used in this research is the effect of Murabahah, Mudharabah,Musyarakah financing while the level of profitability is measured using the financial ratio Return on assets (ROA). Methods: This research uses a quantitative approach with associative research type. The data used in this study is secondary data obtained from the quarterly financial statements of PT. Bank Rakyat Indonesia (BRI) Syariah for the period 2012-2020 with a total sample of 36 data. The analytical method used in this research is descriptive test, data normality test, classical assumption test which multiple linear regression. Conclusion and suggestion:The results of this study indicate that (1) Murabahah financing has a negative and significant effect on ROA profitability,(2) Mudharabah Financing has a positive andsignificant effect on ROA profitability, (3)Musyarakah financing has a positive and significant effect on ROA profitability,Murabahah, Mudharabah, Musyarakah financing has a positive and significant effect on ROA profitability at PT Bank Rakyat Indonesia (BRI) Syariah. Keywords: Murabahah, Mudharabah, Musyarakah Financing and Profitability